2008
DOI: 10.1007/s00300-008-0447-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an HSP70 heat shock response in two Antarctic marine invertebrates

Abstract: Members of the HSP70 gene family comprising the inducible (HSP70) genes and GRP78 (Glucose-regulated protein 78kDa) were identified in an Antarctic sea star (Odontaster validus) and an Antarctic gammarid (Paraceradocus gibber). These genes were surveyed for expression levels via Q-PCR after an acute two-hour heat shock experiment in both animals and a time course assay in O. validus. No significant up-regulation was detected for any of the genes in either of the animals during the acute heat shock. The time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 41 publications
1
54
1
Order By: Relevance
“…Similar down-regulation of several genes (dnaja1, hsp60, hsp70_3 and gdh) at 10 compared to 5°C after LTS was detected in C. glacialis using qPCR. The lack of cellular stress response in Antarctic species is due to adaptation and specialization to stably cold Antarctic waters (Clark et al 2008, Bilyk & Cheng 2014. Although environmental conditions in the Arctic Ocean are more variable then in the Antarctic (Clarke & Peck 1991), and the lack of cellular stress response has not been reported in Arctic species, the lack of thermal stress response in C. glacialis may be explained by cold-water specialization.…”
Section: Lack Of Thermal Stress Response In C Glacialismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar down-regulation of several genes (dnaja1, hsp60, hsp70_3 and gdh) at 10 compared to 5°C after LTS was detected in C. glacialis using qPCR. The lack of cellular stress response in Antarctic species is due to adaptation and specialization to stably cold Antarctic waters (Clark et al 2008, Bilyk & Cheng 2014. Although environmental conditions in the Arctic Ocean are more variable then in the Antarctic (Clarke & Peck 1991), and the lack of cellular stress response has not been reported in Arctic species, the lack of thermal stress response in C. glacialis may be explained by cold-water specialization.…”
Section: Lack Of Thermal Stress Response In C Glacialismentioning
confidence: 99%
“…Trematomus bernacchii) (Buckley & Somero 2009) to invertebrates (La Terza et al 2001, Clark et al 2008. In most cases only heat shock response, particularly expression of HSP70, was in - vestigated and absence of HSP up-regulation was detected.…”
Section: Lack Of Thermal Stress Response In C Glacialismentioning
confidence: 99%
“…For example, the enhanced expression of GRP78 has been described in response to heat in diverse temperate species such as the Atlantic salmon Salmo salar (Lund et al 2002), the oyster Crassostrea gigas (Yokoyama et al 2006) and the crustacean Fenneropenaeus chinensis (Luan et al 2009). However, this mechanism is absent in mammalian and rainbow trout Oncorhynchus mykiss cell lines (Kozutsumi et al 1989;Ojima et al 2005) and the Antarctic invertebrates Odontaster validus and Paraceradochus gibber (Clark et al 2008d). There is now an increasing number of examples of both HSP70 and HSC70 being induced in response to heat in marine species (reviewed in Place et al 2008).…”
Section: Hsp70 Gene Family Expressionmentioning
confidence: 99%
“…Significant differences of Le-SOD expression levels between the groups of small individuals were identified using an unpaired t test with Welch correction for unequal variances or the nonparametric Mann-Whitney test pathways involving NFκB as found in the disk abalone Haliotis discus discus (De Zoysa et al 2009;Ju et al 2007). Whereas some Antarctic marine invertebrates such as the sea star Odontaster validus or the gammarid Paraceradocus gibber lack a classical heat shock response (Clark et al 2008b;Clark and Peck 2009), experimental work with L. elliptica indicated that the HSP70 genes are induced in response to heat stress (Clark et al 2008a;Park et al 2007), hypoxia (Clark and Peck 2009;Clark et al 2013), and also changes in pH (Cummings et al 2011). HSPs are often involved in stress defense and have been shown to be upregulated in hemocytes upon microbial challenge in bay scallops (Argopecten irradians) and zebra mussels (Dreissena polymorpha) (Xu and Faisal 2009;Song et al (2006).…”
mentioning
confidence: 99%